2012
DOI: 10.1111/j.1469-7610.2012.02620.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Psychosocial adjustment and mental health in former child soldiers – a systematic review of the literature and recommendations for future research

Abstract: Aims and scope This article reviews the available quantitative research on psychosocial adjustment and mental health among children (age <18 years) associated with armed forces and armed groups (CAAFAG) – commonly referred to as child soldiers. Methods PRISMA standards for systematic reviews were used to search PubMed, PsycInfo, JSTOR, and Sociological Abstracts in February 2012 for all articles on former child soldiers and CAAFAG. Twenty-one quantitative studies from 10 countries were analyzed for author, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
173
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(188 citation statements)
references
References 77 publications
(194 reference statements)
9
173
1
5
Order By: Relevance
“…For example, non-WEIRD populations are more likely to be exposed to war and political violence (18,19). Children in non-WEIRD populations are also more likely to be exposed to war as both civilians and combatants (20). WEIRD cultures may also atypically influence the nature and sources of psychological resilience to early life adversity.…”
mentioning
confidence: 99%
“…For example, non-WEIRD populations are more likely to be exposed to war and political violence (18,19). Children in non-WEIRD populations are also more likely to be exposed to war as both civilians and combatants (20). WEIRD cultures may also atypically influence the nature and sources of psychological resilience to early life adversity.…”
mentioning
confidence: 99%
“…The review also identified only two studies focused on the early childhood period, even though this area understandably is regarded as the most costeffective period for preventive efforts (Heckman, 2006;Shonkoff & Garner, 2012). Authors of similar reviews have all emphasized that an important future research direction among conflict-affected children and adolescents concerns contextually sensitive longitudinal epidemiological research focused on identifying modifiable risk and protective factors at multiple levels of the social ecology (e.g., individual-, family-, school-, community-levels) (Reed et al, 2012;Betancourt et al, 2013). Such a multi-level model research could, for instance, focus on family-level variables by sampling family units rather than individuals within households (Farhood et al, 1993), which is the current norm.…”
mentioning
confidence: 99%
“…Indirect exposure to violence, through television or radio broadcasts, is another source of trauma (e.g., see Hadi & Llabre, 1998;Macksoud & Aber, 1996;Thabet, Ibraheem, Shivram, Winter, & Vostanis, 2009). Children and adolescents are also involved in the hostilities (e.g., see Amone-P'Olak, 2005;Bayer, Klasen, & Adam, 2007;Betancourt, Borisova, et al, 2013;Derluyn et al, 2004;Macksoud & Aber, 1996;Robinson, 2013;Sack, Him, & Dickason, 1999), either training with armed forces, patrolling, or being forced to commit acts of violence or subterfuge. In some conflicts, girls are abducted by rebel forces and forced into marriage or other types of sexual abuse as reported among girls abducted in Northern Uganda (Amone-P'Olak, 2005).…”
Section: Safetymentioning
confidence: 99%